2015
DOI: 10.1002/ijc.29583
|View full text |Cite
|
Sign up to set email alerts
|

Leukemic progenitor cells are susceptible to targeting by stimulated cytotoxic T cells against immunogenic leukemia‐associated antigens

Abstract: Leukemic stem cells (LSC) might be the source for leukemic disease self-renewal and account for disease relapse after treatment, which makes them a critical target for further therapeutic options. We investigated the role of cytotoxic T-lymphocytes (CTL) counteracting and recognizing LSC. Leukemia-associated antigens (LAA) represent immunogenic structures to target LSC. We enriched the LSC-containing fraction of 20 AML patients and hematopoietic stem cells (HSC) of healthy volunteers. Using microarray analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 49 publications
0
14
0
4
Order By: Relevance
“…Although it remains controversial whether allogeneic stem cell transplantation can alleviate the negative prognostic impact of adverse cytogenetics, it was recently demonstrated that leukemia stem cells, which are thought to account for relapse after therapy, highly express leukemiaassociated Ags and could be targeted by T cells. 22 Furthermore, leukemia-associated Ags-peptide specific T cells were detected in nearly all AML patients after allogeneic stem cell transplantation, supporting the concept of potential immunologic control of highrisk AML after aHCT. 23 Although higher patient age was not associated with shorter OS in our cohort, interestingly CR at the time of aHCT was not a positive factor for OS, although it was associated with a lower relapse rate in the univariate analysis.…”
Section: Discussionmentioning
confidence: 69%
“…Although it remains controversial whether allogeneic stem cell transplantation can alleviate the negative prognostic impact of adverse cytogenetics, it was recently demonstrated that leukemia stem cells, which are thought to account for relapse after therapy, highly express leukemiaassociated Ags and could be targeted by T cells. 22 Furthermore, leukemia-associated Ags-peptide specific T cells were detected in nearly all AML patients after allogeneic stem cell transplantation, supporting the concept of potential immunologic control of highrisk AML after aHCT. 23 Although higher patient age was not associated with shorter OS in our cohort, interestingly CR at the time of aHCT was not a positive factor for OS, although it was associated with a lower relapse rate in the univariate analysis.…”
Section: Discussionmentioning
confidence: 69%
“…We used this approach to account for the lack within-study healthy controls in the curated gene expression datasets. To address this issue, we used 5 additional datasets the included within-study controls, GEO accessions: GSE107968, GSE68172 58 , GSE17054 59 , GSE33223 60 , and GSE15061 61 (Table 1B). We refer to the latter datasets hereafter as “covariate” reference datasets, as they were as the reference datasets in the batch correction.…”
Section: Methodsmentioning
confidence: 99%
“…Самые чув-ствительные системы для проведения полимеразной цепной реакции позволяли определять экспрессию PRAME у здоровых доноров. Однако активность гена у больных была выше как минимум на порядок [13][14][15][16][17].…”
Section: подходы используемые при определении уровня экспрессии Pramunclassified